Exploring catalase inhibition as an adjuvant to antimicrobial photodynamic therapy against Staphylococcus aureus - Surur, Amanda Koberstain [UNESP]; de Santana, Renata Laurintino [UNESP]; Palhares, Amanda Leal [UNESP]; de Oliveira, Analú Barros [UNESP]; De Annunzio, Sarah Raquel [UNESP]; de Souza de Santana, Willian Max Oliveira [UNESP]; Brighenti, Fernanda Lourenção [UNESP]; Bagnato, Vanderlei Salvador; Fontana, Carla Raquel [UNESP] (Springer Nature, 2025)
An alternative approach to addressing the irrational use of antimicrobials is antimicrobial photodynamic therapy (aPDT). This modern and non-invasive form of therapy has its mechanism of action based on the activation of a photosensitizer (PS) by irradiation in the presence of oxygen and under specific light fluences at the appropriate wavelength. As a protective mechanism, certain bacterial species exhibit an enzymatic antioxidant system to protect against the harmful effects of reactive species, with catalase being an important enzyme within this system. This study aimed to evaluate whether there is a synergistic effect between catalase inhibition and methylene blue (MB) and curcumin (CUR)-mediated aPDT on methicillin-sensitive S. aureus ATCC 25923 in suspension and in 24 h biofilm, in this article called combined terapy (CT). In suspension, MB-mediated CT achieved total bacterial reduction with 30 min of catalase inhibition, whereas CUR-mediated CT achieved total reduction with 10 min of enzymatic inhibition. In biofilms, CUR-mediated CT did not show significant bacterial reduction in any of the inhibition times evaluated. In contrast, MB-mediated CT with 30 min of catalase inhibition damaged extracellular matrix proteins. Therefore, it can be concluded that the synergistic action between catalase inhibition and MB-mediated aPDT has been proven, and the treatment has great potential for future clinical applications involving S. aureus infections.